IDENTIFICATION OF MOLECULAR MARKERS LINKED TO LEAF CURL VIRUS DISEASE RESISTANCE IN COTTON (Journal of Sciences, Islamic Republic of Iran)
The identification of molecular markers linked to leaf curl virus (CLCuV) disease resistance in cotton has the potential to improve both the efficiency and the efficacy of selection in cotton breeding programs. Genetic analysis suggested that CLCuV resistance is controlled by a single dominant gene. In this study, an interspecific F2 population derived from a cross of Gossypium barbadense and Gossypium hirsutum was phenotypically classified into CLCuV susceptible and resistant plants. A subset of these F2 plants was evaluated by selective genotyping, with restriction fragment length polymorphism (RFLP) to identify DNA markers linked to the CLCuV resistance gene. Sixty seven F2 derived F3 families were evaluated for segregation at 137 RFLP loci. Three DNA marker loci, linked to each other, also showed significant association with CLCuV resistance. Sequencing of linked markers will permit locus-specific DNA primers for use in PCR-based identification of CLCuV-resistant plants in breeding populations.